2009
DOI: 10.1007/s10165-009-0218-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tacrolimus for lupus nephritis: a placebo-controlled double-blind multicenter study

Abstract: We evaluated the efficacy and safety of tacrolimus in patients receiving glucocorticoid therapy for lupus nephritis. Patients with persistent nephritis were randomized to receive 28 weeks of double-blind treatment with tacrolimus (3 mg/day) or placebo. The primary endpoint was the change in the lupus nephritis disease activity index (LNDAI) calculated from scores for daily urinary protein excretion, urinary red cells, serum creatinine, anti-double-stranded DNA antibody, and serum complement. Statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 33 publications
(31 reference statements)
2
38
0
1
Order By: Relevance
“…In the present surveillance study, the efficacy of MZR was confirmed based on composite indicators. Numerous reports have been published recently showing that MMF and tacrolimus are effective in terms of providing satisfactory improvements in urine protein [17][18][19]. In the present study, decreases in urine protein levels were also confirmed, and the efficacy of MZR was demonstrated.…”
Section: Efficacysupporting
confidence: 71%
See 1 more Smart Citation
“…In the present surveillance study, the efficacy of MZR was confirmed based on composite indicators. Numerous reports have been published recently showing that MMF and tacrolimus are effective in terms of providing satisfactory improvements in urine protein [17][18][19]. In the present study, decreases in urine protein levels were also confirmed, and the efficacy of MZR was demonstrated.…”
Section: Efficacysupporting
confidence: 71%
“…In such cases, decreased renal function, which is one of the ADRs to immunosuppressants, due to long-term treatment is a concern [17,20]. In the present surveillance study, ADRs related to decreased renal function included 1 case of renal impairment and 2 cases of blood creatinine increased.…”
Section: Renal Functionmentioning
confidence: 96%
“…The researchers found that after the treatment, proteinuria was significantly reduced and seven of the nine patients showed a complete clinical response. In a RCT comparing tacrolimus to placebo in 63 patients with LN who had persistent nephritis despite glucocorticoids, tacrolimus was associated with a decrease in LN disease activity index compared with placebo over 28 weeks of treatment (40). In another open-labeled, prospective study of nine patients with diffuse proliferative LN who had persistent proteinuria (.1 g) despite intravenous cyclophosphamide therapy, tacrolimus (0.1 mg/kg per day) was administered for 1 year with target drug levels (4-10 mg/L).…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…We evaluated the adverse events related to TAC administration (i.e., kidney dysfunction and impaired glucose tolerance) based on the results of an early phase II study of TAC for rheumatoid arthritis and a phase III study of TAC for lupus nephritis (1,2). The criteria for kidney dysfunction during the TAC administration period included either 1) a !…”
Section: Adverse Events Related To Cnismentioning
confidence: 99%
“…Calcineurin inhibitors (CNIs) such as tacrolimus (TAC) and cyclosporin A (CSA) are immunosuppressive drugs that inhibit nuclear factor-κB (NF-κB) activity and are used in organ transplantation and to treat connective tissue diseases (CTDs) (1)(2)(3)(4). There are remarkable inter-and intraindividual variabilities in their pharmacokinetics of these nal ulceration.…”
Section: Introductionmentioning
confidence: 99%